Relationship between personality and social network characteristics - Valentová, Klára (Jihočeská univerzita, 2021)
This thesis investigated whether an individual's personality (assessed on four personality dimensions: Friendliness, Activity/Excitability, Confidence, Openness) can be related to its social network position in Barbary macaques (Macaca sylvanus). The effect of sex and rank was also evaluated. The network position of individuals was described by individual network characteristics values generated via social network analysis. Additionally, the phenotypic based assortment within the studied group was examined. The results showed that personality is related with the position of the individual in its social group and assortment based on several personality dimensions was found in studied networks.
Relationship between personality and social network characteristics
Keywords: animal social network; personality; assortment